The Influence of Fear of Missing Out, Hedonic Shopping Motivation, Flash Sales on Impulse Buying Smartwatches - Muhammad Asyam Taqi Abrar (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to provide empirical evidence regarding the influence of Fear Of Missing Out, Hedonic Shopping Motivation, Flash Sale on Impulse Buying of Shopee Smartwatches both partially and simultaneously. This study was conducted on Shopee customers who purchased Smartwatches, hypothesis testing was carried out using the SPSS24 application. The number of populations in this study was not known with certainty, sampling was carried out using the unknown population formula with a total of 100 samples. Based on the results of the study, it can be seen that the variables Fear Of Missing Out, Hedonic Shopping Motivation, Flash Sale have a significant influence partially and simultaneously on Impulse Buying of Shopee Smartwatches